Investigation of the stomata size and frequency of grapevine (Vitis vinifera L.) cultivar ‘Kékfrankos’ - Bodor, Péter; Szekszárdi, Andrea; Varga, Zsuzsanna; Baló, Borbála (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2019)
Grapevine (Vitis vinifera L.) leaves show high morphological diversity alongside the shoot. This variability has been investigated in this study to explore the change in leaf size, leaf thickness, stomata density and stomata size among the 1st, 5th and 10th leaves on the main shoots and leaves on the laterals. Results showed that leaf size altered from the basal abaxial leaves to the middle of the shoot, while the laterals had the smallest leaves. Number of stomata also varied significantly regarding the different levels of the canopy. First leaves on the shoots had the least stomata per unit leaf area while this number increased above. In contrast with this the size, i.e. length and width of the stomata did not differ. Leaf thickness was the lowest on the leaves of the lateral shoots, while the values decreased from the 1st to the 10th nodes. These results raised the question about the ontogeny and heteroblasty of the grapevine foliage.